New Understanding of the Relevant Role of LINE-1 Retrotransposition in Human Disease and Immune Modulation - Zhang, Xiao; Zhang, Rui; Yu, Jinpu (Frontiers in Cell and Developmental Biology, 2020)
Long interspersed nuclear element-1 (LINE-1) retrotransposition is a major hallmark of cancer accompanied by global chromosomal instability, genomic instability and genetic heterogeneity and has become one indicator for the occurrence, development and poor prognosis of many diseases. LINE-1 also modulates the immune system and affects the immune microenvironment in a variety of ways. Aberrant expression of LINE-1 retrotransposon can provide strong stimuli for an innate immune response, activate the immune system, and induce autoimmunity and inflammation. Therefore, inhibition the activity of LINE-1 has become a potential treatment strategy for various diseases. In this review, we discussed the components and regulatory mechanisms involved with LINE-1, its correlations with disease and immunity, and multiple inhibitors of LINE-1, providing a new understanding of LINE-1.